2016
DOI: 10.5505/tjtes.2016.48979
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin prevents postoperative formation of intra-abdominal adhesions in a rat model: An experimental study

Abstract: Results indicated that cordycepin effectively reduced adhesion in a rat abrasion model. Thus, this agent may be valuable to prevent postoperative adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…In this study, erythrocyte and plasma MDA levels were found to be more important in the control group compared to heparin and sham group. It is observed that this result [7,9,10,12,40] is consistent with the notifications of the researchers. The increase in MDA in the control group is caused by cleavage of lipid-containing structures such as plasma and cell membranes of oxygen radicals by the cells involved in the inflammatory response during the adventitious process [28,43].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, erythrocyte and plasma MDA levels were found to be more important in the control group compared to heparin and sham group. It is observed that this result [7,9,10,12,40] is consistent with the notifications of the researchers. The increase in MDA in the control group is caused by cleavage of lipid-containing structures such as plasma and cell membranes of oxygen radicals by the cells involved in the inflammatory response during the adventitious process [28,43].…”
Section: Discussionsupporting
confidence: 91%
“…GSH level was found to be more important in the control group compared to heparin and sham group. It was seen that the results were similar to the findings of [7,9]. GSH plays a central physiological role in protecting against endogenous and exogenous oxidants, toxic substances, DNA damaging agents and carcinogens, and maintaining body haemostasis and thus it clears oxygen radicals in the environment by maintaining intracellular GSH synthesis [20,39].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, ELA may also improve vascular congestion caused by widely used drugs such as fluoxetine. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in surgical techniques, adhesion development after abdominal surgery remains a problem [ 1 4 ]. Peritoneal damage during surgery, damaged serosal surfaces, tissue ischemia, the presence of foreign materials in the environment, increased vascular permeability on the background, fibroblastic activity with underlying decreased fibrinolytic activity with growth factors, and inflammatory cytokines can cause intra-abdominal adhesions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%